2020
DOI: 10.11646/zootaxa.4851.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anuran species diversity of the Panna Tiger Reserve, Central India, using an integrated approach

Abstract: We present a comprehensive inventory of amphibians from Panna Tiger Reserve in Madhya Pradesh based on morphological, molecular and bioacoustic data. Representatives of 15 anuran species were collected, corresponding to roughly four fifths of the known amphibian species of Madhya Pradesh. The main results of this study are: (1) Description of advertisement calls of eleven species, including the first-time description of advertisement calls of Sphaerotheca pashchima. (2) Identification of cryptic species using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 473 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Our delimitation analysis reconfirmed this species to be S. pashchima. Prasad et al (2020) genetically confirmed the presence of the species in the Panna Tiger Reserve in Madhya Pradesh. Our study also confirmed the occurrence of S. pashchima in eastern Maharashtra, extending the species' range into central India (Fig.…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L Esupporting
confidence: 55%
“…Our delimitation analysis reconfirmed this species to be S. pashchima. Prasad et al (2020) genetically confirmed the presence of the species in the Panna Tiger Reserve in Madhya Pradesh. Our study also confirmed the occurrence of S. pashchima in eastern Maharashtra, extending the species' range into central India (Fig.…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L Esupporting
confidence: 55%
“…Males acquire bright yellow colour during breeding season to attract females. Snout-Vent Length: 65-158 mm (Boulenger, 1920); 16-161 mm (Sanyal et al, 1991); 89-137 mm ; 17-154 mm (Sarkar et al, 1992); 71.0-88.5 mm ; 62 mm ; 52-143 (Ray and Tilak, 1995); 134 mm ; 20-159 mm ; 72-143 mm (Sarkar and Ray, 2006); 54-94 and 50-144 mm (Deuti et al, 2014); 41.22-85.64 and 60-150 mm (Deuti et al, 2017); male 153.9 mm (Prasad et al, 2020).…”
Section: Husain and Hasan International Journal Of Agricultural And Applied Sciences 2(1)mentioning
confidence: 99%
“…Hand book Indian amphibians: 28, 265;Sarkar et al, 2004. Fauna of Bihar (including Jharkhand) (Sarkar et al, 1992;; subarticular tubercles blunt, mixed with flat palmer glands; palmer tubercle distinct, triangular and wider in front; toes more than 1/2 nd to 2/3 rd webbed, two phalanges of 4 th toe free; toes 2/3 rd webbed (Ray, 1999; or scarcely webbed (Prasad et al, 2020); subarticular tubercles small; inner and outer metatarsal tubercles sharp-edged and equal sized ; tibio-tarsal articulation reaching between tympanum and eye (Sarkar et al, 1992; or hind edge of eye (Ray, 1999;Husain et al, 2020) or between shoulder and eye . Colouration: Brownish, greyish or olive-brown with smooth warts and mixed grey blotches; fingertips black; vocal sac of calling male white or yellowish.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations